Desempenho, características da carcaça e da carne de bovinos de diferentes sexos e idades, terminados em confinamento - Santos, Angélica Pereira dos (2005)
The objective of this experiment was to evaluate the performance, carcass and meat characteristics of 24 castrated male bovines, being 12 with average initial age of 8.1 months and 12 with 20 months. Also were used 24 females, being 12 with average initial age of 8.2 months and 12 with 20.5 months. This animals were took by chance from the experimental herb of cattle of Departamento de Zootecnia da UFSM, being ⅝ Charolais (CH) ⅜ Nellore (NE), ⅝NE ⅜CH, ¾CH ¼NE and ¾NE ¼CH genetic groups, with age: young (animals slaughtered with age between 20 and 24 months), or superyoung (animals slaughtered with age between 12 and 16 months). The average age on final experimental period, for young animals was of 22.5 and 22 months for females and males and for superyoung was of 15.2 and 13.1 months for females and males, respectively. The animals were feedlot finished until them reach the previously established slaughter weight of 360 kg for females and 330 kg for males. The diet was calculated by NRC (1996), objecting an average daily weight gain (DWG) of 1.30 kg/animal, and estimating a dry matter intake (DMI) for percentage of live weight (DMILW) of 2.5 kg of dry matter (DM)/100 kg of live weight. For all animals, the utilized diet showed a roughage:concentrate rate of 50:50 (on DM base), containing 16% of crude protein (CP) for superyoung and 13% CP for youngs. The complete randomized experimental design was used, in a 2 x 2 factorial arrangement (two ages and two sex. Each treatment was composed by 3 repetitions, were a experimental unity was constituted by one lot of four animals (Capitulum 1), and Capitulum 2 and 3 each treatments was composed by 12 repetitions, were a experimental unity was constituted by one animal. The males showed higher average DWG (1.36 vs. 1.26 kg) in relation to females. The young age showed higher average DWG (1.55 vs. 1.07 kg). Verifying a similar behavior for daily body condition gain (.015 vs. .009 points) and young in relation to superyoungs. Initial weight (IW), initial and final body condition (IBC and FBC), daily dry matter intake (DDMI), per live (DMILW) and metabolic weights (DMIMW), digestible energy (DE) and protein (DP) conversions parameters were influenced by sex and age. For IW, IBC and DDMI, young females were superior them contemporaneous males (256.63 vs. 230.63 kg; 2.50 vs. 2.38 ptos and 8.96 vs. 8.37 kg, respectively); to superyoung any sex effect was observed. For FBC, superyoung females were superior them males (3.95 vs. 3.80 ptos). Where young animals had higher DMILW and DMIMW and best DE and DP, however, not differed between sex; but superyoung, males were superior than females (2.74 vs. 2.47%; 108.09 vs. 101.92 g; 27.30 vs. 38.01 kg DE/kg WG and 1.19 vs. 1.72 kg CP/kg WG, respectively). Superyoung age showed higher hot and cold carcass weights (196.79 and 192.03 vs. 186.93 and 181.85 kg), hot and cold carcass dressing percentage (56.80 and 55.42 vs. 54.26 and 52.58 %), best conformation (10.83 vs. 9.00 points) and higher forequarter absolute weight and percentage (35.15 vs. 32.58 kg and 36.65 vs. 35.94 %). Males carcasses showed higher arm perimeter (34.65 vs. 33.62 cm), Longissimus dorsi area (58.55 vs. 58.27 cm2) and physiologic maturity (13.21 vs. 13.17 points). Cushion thickness (CT), Longissimus dorsi area/100 kg cold carcass weight (LDA100), leg length (LL), subcutaneous fat thickness in mm and per 100 kg of cold carcass (SFT and SFT100) and sidecut (Sid, kg and %) showed interaction between sex and age. For CT, was observed that superyoung males showed higher CT comparing to young and to superyoung females, althought this last ones not differed from young. Superyoung males showed higher LDA100 then females (33.70 vs. 28.95 cm2); for young age any difference was observed between sex. Lesser LL was observed to superyoung males, differing from the other age and sex. For SFT, SFT100, Sid, kg and %, superyoung females presented carcasses with lesser fat percentage (20.03 vs. 22.79%), muscle:bone rate (4.11 vs. 4.40) and muscle + fat:bone (5.39 vs. 5.99); higher bone percentage (15.76 vs. 14.45%) and muscle:fat (3.29 vs. 2.87); meat with best texture (3.92 vs. 4.38 ptos) and higher chilling loss (8.53 vs. 5.07%). The males showed carcass with higher muscle percentage (65.54 vs. 62.03%), bone (15.48 vs. 14.73%) and muscle:fat rate (3.46 vs. 2.69); lesser fat percentage (23.58 vs. 19.25%), muscle + fat:bone rate (5.52 vs. 5.86); and meat with higher palatability (7.33 vs. 6.22 ptos) and lesser marbling (3.79 vs. 5.58 ptos). Cocking loss and total fat quantity presented interaction between sex and age. Males meat from both age showed higher cocking losses, comparing to superyoung females, althought this last ones not differed from young. For total fat quantity was verified that superyoung females were superior (51.07 kg), and young males were lesser (32.02 kf), differing to other age and sex